A meta-analysis on the risk of esophageal cancer in type 2 diabetes patients treated with GLP-1 receptor agonists - Wu, Qi; Zeng, Yan; Liu, Yong; Teng, Fangyuan; Zhou, Tiejun; Guo, Man; Jiang, Zongzhe; Xu, Yong (Frontiers in Endocrinology, 2025)
ObjectiveTo evaluate the association between glucagon-like peptide-1 receptor agonists (GLP-1 RAs) treatment and the risk of esophageal cancer in adults with type 2 diabetes mellitus (T2DM) or obesity through a comprehensive meta-analysis.MethodsA systematic computerized searches and collection of eligible randomized controlled trials (RCTs) was performed to compare the risk of esophageal cancer between GLP-1 RA and control agents. The bias risks and quality of the studies were evaluated, and a meta-analysis was conducted using Stata 18.0 and R 4.0.2 statistical software.ResultsThe meta-analysis included data from six studies involving 13,391 participants. The pooled relative risk (RR) of esophageal cancer in patients using GLP-1 RAs compared to control agents was 0.46 (95% CI 0.13-1.59; p=0.725; I²=0%). Subgroup analyses stratified by age groups, intervention durations, BMI categories, and indications for T2DM or obesity treatment more often indicated no association between GLP-1 RAs use and increased risk of esophageal cancer.ConclusionsGLP-1 RAs did not increase the incidence of esophageal neoplasms, and there were not probably significant within-class differences in T2DM or obesity treatment. This finding supports the safety of GLP-1 RAs as a therapeutic option for the clinical management of T2DM.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42024543945.